Designing a Health-Orientation Ranking Model for Employers in Iran - Behzad Damari; Hosein Almadani; Gholamreza Bostanmanesh; Aref Vahabzadeh; Sahand Riazi-Isfahani (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Employment is amongst fundamental social determinants of health. It is in the center of attention of major national policies and strategies of the countries considering economics, equity in health, employment and decent work. The purpose of this study was to design a model for ranking the health-orientation of employers in order to increase their social accountability. Materials and Methods: This study was conducted in a qualitative approach. Data were collected via review of the literature, and focused group discussions with nine experts form five related areas. Based on the results of the group discussion, a draft of the charter for health ranking of the employers was drafted and finalized by the technical steering committee meeting. The final product of this study is the health-orientation ranking of the employers and the corresponding indicators. Results: The charter consists of three main components including goal, process, and regulatory necessities. Twenty four indicators in four groups were proposed for assessing the health-orientation of the employers including 1. Management interventions in workplace, 2. Safety interventions and accident reduction, 3. Interventions for reducing risk factors for employees and families, and 4. Compliance with environmental principles in the production cycle to the consumption of the product. Conclusion: The integration of all four dimensions of health and effective factors, and the social accountability in this ranking model, as well as the participation of the High Association of Employers in the country and the Higher Workers Association are the key qualities of this study. It is suggested that the implementation of the model be by self-declaration in the first year. DOI: http://doi.org/10.22037/ch.v5i4.19055